2013
DOI: 10.1590/s0102-86502013000900010
|View full text |Cite
|
Sign up to set email alerts
|

Virtual planning and construction of prototyped surgical guide in implant surgery with maxillary sinus bone graft

Abstract: PURPOSE:To evaluate the efficacy of associating techniques of bone grafting in the maxillary sinus with the use of a prototyped surgical guide for planning and positioning dental implants in total edentulous maxillae, rehabilitated after six months. METHODS:Eight patients consecutives with totally edentulous maxilla presenting few remaining bone in the posterior alveolar ridge, associated with pneumatization of the maxillary sinus were selected. Twenty eight Brånemark RP 10mm implants were installed in 14 maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Martins and Lederman in 2013, evaluated the efficacy of virtual planning using DentalSlice software and revealed that a prototype guide planned on DentalSlice was efficient for positioning implants and for quantifying and locating the bone graft, which also aided in the achievement of 100% success rate. [ 13 ] In 2012, Nkenke et al . even promoted the implementation of virtual dental implant-planning software in dental undergraduate curriculum based on their assessment of positive acceptance of the software by the students.…”
Section: Computed Tomography Based Implant-planning Softwaresmentioning
confidence: 99%
“…Martins and Lederman in 2013, evaluated the efficacy of virtual planning using DentalSlice software and revealed that a prototype guide planned on DentalSlice was efficient for positioning implants and for quantifying and locating the bone graft, which also aided in the achievement of 100% success rate. [ 13 ] In 2012, Nkenke et al . even promoted the implementation of virtual dental implant-planning software in dental undergraduate curriculum based on their assessment of positive acceptance of the software by the students.…”
Section: Computed Tomography Based Implant-planning Softwaresmentioning
confidence: 99%